Integration of DEM derived depression and SCS based runoff datasets for delineation of potential rainwater harvesting sites in Sita and Swarna basins, Karnataka - B., ANIL; G, SHIVANNA; VINAYA, M.S. (Journal of Soil and Water Conservation, 2020)
A large amount of rainwater is lost due to surface runoff that reaches the sea through streams and rivers. Rainwater Harvesting (RWH) is an encouraging approach to store available surface water and improve groundwater to overcome the water dearth problems. The present study utilizes a technically robust Geographic Information System (GIS) based methodology for evaluating and identifying the suitable RWH sites depending on the depth and volume of depressions derived from ASTER-DEM. The procedure primarily developed for the humid and tropical climatic regions has been adopted for the Sita and Swarna River basins of Southern Coastal Karnataka in the present study. The selection of a suitable site for RWH is based on different key determinants such as land use/land cover, hydrology, soil, and topography as well as the surface runoff derived using the ArcCN-Runoff tool. Initially, ninety four depression parcels have been extracted in Sita River and Swarna River basins from the DEM data using algebraic operations. Subsequently, key determinants have been analyzed in GIS domain as per the criteria mentioned in the Integrated Mission for Sustainable Development (IMSD) guidelines. As per the GIS analysis, total thirty depression parcels have been considered in the study, out of which eight parcels are classified as highly suitable; twelve as moderately suitable, and the remaining ten as not suitable RWH sites. If the rainwater is reaped and conserved properly using the suggested RWH sites as per the IMSD guidelines, the study area can serve 341.4 million cubic meters of additional water for domestic, irrigation and small scale industrial sectors. The delineated RWH sites are subjected to ground verification at 30% sample sites using ArcPad Mobile GIS unit. The resulted accuracy is found to be 89%. The study emphasizes the benefits of GIS techniques over the traditional survey methods for sustainable water conservation. However, it is recommended to employ cadastral level data which enables easy acquisition of land required for constructing the RWH structures at farm and private lands.